Accelerated forgetting is sensitive to β‐amyloid pathology and cerebral atrophy in cognitively normal 72‐year‐olds: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Lu, Kirsty; Pavisic, Ivanna M.; James, Sarah‐Naomi; Street, Rebecca E.; Keuss, Sarah E.; Buchanan, Sarah M.; Wagen, Aaron; Storey, Mathew; Parker, Thomas D.; Lane, Christopher A.; Keshavan, Ashvini; Murray‐Smith, Heidi; et al.
Abstract: Background: Accelerated Forgetting (AF) is the phenomenon whereby material is retained normally over short intervals (minutes or hours) but forgotten abnormally rapidly over longer periods (days or weeks). AF has been observed in presymptomatic carriers of mutations causing familial Alzheimer's disease (AD) (doi:10.1016/S1474‐4422(17)30434‐9). To our knowledge, no studies have investigated whether AF is sensitive to preclinical AD pathology in cognitively‐normal older adults. Method: Participants in the Insight 46 study, a sub‐study of the British 1946 birth cohort, completed baseline cognitive and neuroimaging assessments at age 69‐71. For the follow‐up visits (∼29 months later), we complemented the clinic visit assessments of Complex Figure Drawing and the Face‐Name test (FNAME‐12) with a 7‐day delay version administered by telephone (Figure 1). AF scores were calculated as the percentage of material retained after 7 days, relative to retention after 30 minutes. Cerebral atrophy between baseline and follow‐up was quantified from T1‐weighted MRI using the Brain Boundary Shift Integral (BBSI). β‐amyloid status at baseline (positive / negative) was determined from 18 F‐Florbetapir‐PET. As follow‐up assessments are still underway, preliminary interim analyses have been conducted based on 195 cognitively‐normal individuals with complete neuroimaging data (see Table 1 for characteristics). Multivariable regression models were used to investigate the effects of β‐amyloid status and BBSI on AF, and to explore interactions between these two predictors, adjusting for potential confounders including prospectively‐collected measures of childhood cognitive ability and education. Result: Despite no statistically‐significant differences after a 30‐minute delay, β‐amyloid‐positive participants retained a lower percentage of Complex Figure material over 7 days (71.8% vs. 80.7%, p =0.010) and a trend to a lower percentage of FNAME‐12 material (69.4% vs. 77.2%, p = 0.083) (Table 2, Figure 2). Higher education predicted better retention of the Complex Figure. Among β‐amyloid‐positive participants only, greater cerebral atrophy predicted poorer retention of the Complex Figure (Table 2, Figure 3). Conclusion: These results provide novel evidence of AF in cognitively‐normal β‐amyloid‐positive 72‐year‐olds. AF may be a sensitive outcome measure for therapeutic trials in preclinical AD, as it may reveal subtle memory decline at an earlier stage than traditional assessments. The interaction between β‐amyloid pathology and cerebral atrophy merits longitudinal investigation.